Vegetative Growth Response of Corn (Zea mays) to Actinomycetes, Azospirillum, and Azotobacter Isolated from the Rhizosphere of Neem (Azadirachta indica) - Yusminah Hala; A. Irma Suryani; Octavia Cisiliana Devi (Jurusan Biologi Universitas Negeri Makassar, 2023)
This research is an experimental study that aims to determine the effect of the application of N2-fixing bacteriaActinomycetes, Azospirillum, and Azotobacter on the vegetative growth parameters of corn plants and on thenitrogen content of corn plants. Parameters for measuring the growth of corn plants include: formation rate ofradicle length, plant height, number of leaves, leaf length, fresh weight of plants, fresh weight of plant roots, dryweight of plants, dry weight of plant roots, total N content in plants, as well as physical and chemical qualities ofthe ground. Experiments on the application of N2 -fixing bacteria on corn plants on a laboratory scale were carriedout to determine the in vitro effect of microbes on corn seeds. The pot test was carried out to determine the effectof N2-fixing bacteria on the vegetative growth of corn plants in vivo. Data were analyzed using ANOVA withDuncan's test. The results showed that corn plants inoculated with Actinomycetes, Azospirillum and Azotobactershowed a significant different growth from corn plants without nitrogen fixing bacteria, namely formation rate ofradicle length, plant height, number of leaves, leaf length, fresh weight, dry weight, total N content (%) of crops,and soil physical and chemical quality. It can be concluded that the inoculation of nitrogen-fixing bacteria in cornplants has a significant effect on plant vegetative growth parameters and plant nitrogen content.